2009
DOI: 10.1080/07399330802694955
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Physical Activity in African American Women

Abstract: Obesity and hypertension are among the international problems for which health professionals urge exercise. Exercise might increase if advisers knew how patients normally expend energy. Using the Yale Physical Activity Survey (YPAS), this U.S. study measured energy expenditure in several dimensions of physical activity including exercise, in African American women with hypertension (N = 100). Over half expended at least 6,000 (kilocalories) kcal per week; most expended over 3,500 of those kcal in everyday work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In contrast to reported demographics of participants in walking intervention studies, most (65 percent) participants in this project reported being married. Research showed that married participants were more likely to continue in walking programs (Buchholz & Artinian, ). The majority of the participants reported full‐time employment (55 percent).…”
Section: Discussion Of Findings and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to reported demographics of participants in walking intervention studies, most (65 percent) participants in this project reported being married. Research showed that married participants were more likely to continue in walking programs (Buchholz & Artinian, ). The majority of the participants reported full‐time employment (55 percent).…”
Section: Discussion Of Findings and Outcomesmentioning
confidence: 99%
“…When health care providers are prescribing interventions to increase physical activity, it's important that they select an intervention that doesn't just consider episodic exercise but considers everyday work, such as household chores as a form of physical activity (Buchholz & Artinian, ). Women are more likely to maintain their prescribed physical activity plan when it includes customized activities they enjoy doing and a wide selection of physical activities from which they can chose.…”
Section: Implications For Practicementioning
confidence: 99%
“…Physical activity when skeletal muscles producing bodily movement has been categorized into three levels of intensity of low, moderate, and high [5][6] . This division defines it in three different ways (Table 1).…”
Section: La Participación En El Triatlón Como Necesidad Humana De Defmentioning
confidence: 99%
“…
Buchholz and Artinian (2009) defined physical activity and categorized it into three levels: low, moderate, and high. Triathlon as an activity that typically combines swimming, cycling and running in one event, belongs to high level and is considered as a hard discipline, requiring frequent, well-planned training.
…”
mentioning
confidence: 99%